Effects of boric-acid-applied green tea on the expressions of heat shock proteins in MCF-7 cells - SEZEKLER, IŞIL (CUKUROVA UNIV, FAC MEDICINE, 2019)
Purpose: The study aims to examine the effects of boric acid at different concentrations applied to green tea on heat shock protein (HSP) 70 and HSP 90 in MCF-7 cells. Materials and Methods: Boric acid in sodium tetraborate buffer of 0 mg/m(2) (group 1), 100 mg/m(2) (group 2), 300 mg/m(2) (group 3), and 500 mg/m(2) (group 4) were applied to soil where Camelia sinensis (green tea) grown. The collected green tea leaves were dried and brewed in water at 80 degrees C for 40 minutes. Cytotoxicity was analyzed by MTT method. The prepared green tea extracts (250 mu g/ml) were applied to MCF-7 cells. The mRNA expressions of HSP 70 and HSP 90 were determined by qRT-PCR. The HSP 70 and HSP 90 protein levels were measured by Western blotting method. Results: 100 and 500 mg/m(2) boric-acid-applied green tea extracts increased HSP 90 mRNA expressions in MCF-7 cells compared to green tea extract without boric acid. HSP 70 and HSP 90 protein levels did not show any change between MCF-7 cells with boric-acid-applied green tea extract and green tea extract without boric acid. Conclusion: According to our results, the protein expressions of HSP 70 and HSP 90 in MCF-7 cells changed by neither boric-acid-applied green tea extracts nor green tea extracts without any boric-acid-applied.
Keywords: MCF-7 cells; heat shock protein; green tea; boric acid; cytotoxicity; CANCER; BORON; POLYPHENOLS; INHIBITOR; HSP70